Deep Learning Method to Categorize Attack Patterns for DBI (Deep Brain Implants) - V., Krishnaraj; K., Jaisharma; N., Deepa (International Journal of Psychosocial Rehabilitation, 2020)
DBS stands for Deep Brain Stimulators are used to treat disorders related to neurology in patients by using electrical stimulation. Parkinson disease is treated with such devices. The major issue to be focused on is security, as it deals directly with the human body's emotions as well as physical state. If unattended, this may even lead to the death of a human. Fake stimulation can be used in the human brain to act as an adversary by changing even the emotions of a person. The various attack stimulations can be predicted using a deep learning method in DBS. LSTM (long short-term memory) is used in the proposed system to forecast tremor velocity. The proposed system also identifies stimulations that are genuine. Various attacks were emulated and the proposed system also notifies the patient about the attack